Protective effects of Bacillus licheniformis on growth performance, gut barrier functions, immunity and serum metabolome in lipopolysaccharide-challenged weaned piglets - Yu, Xiaorong; Dai, Zhenglie; Cao, Guangtian; Cui, Zhenchuan; Zhang, Ruiqiang; Xu, Yinglei; Wu, Yanping; Yang, Caimei (Frontiers in Immunology, 2023)
Bacillus licheniformis (B. licheniformis) is a well-accepted probiotic that has many benefits on both humans and animals. This study explored the effects of B. licheniformis on growth performance, intestinal mucosal barrier functions, immunity as well as serum metabolome in the weaned piglets exposed to lipopolysaccharide (LPS). One hundred and twenty piglets were separated into two groups that received a basal diet (the control group, CON), and a basal diet complemented with B. licheniformis (500 mg/kg, the BL group, BL). Twelve piglets were chosen from the above two groups and 6 piglets were injected with LPS intraperitoneally at a concentration of 100 μg/kg and the other half with sterile saline solution of the same volume. All the piglets were sacrificed 4 h after LPS challenge. Results showed that B. licheniformis enhanced the average daily gain (ADG) and ultimate body weight, and lowered the feed-to-weight ratio (F: G) and diarrhea rates. Pre-treatment with B. licheniformis markedly attenuated intestinal mucosal damage induced by LPS challenge. Supplementation with B. licheniformis strengthened immune function and suppressed inflammatory response by elevating the concentrations of serum immunoglobulin (Ig) A and jejunum mucosal IgA and IgG, and decreasing serum IL-6 and jejunum mucosal IL-1β. In addition, B. licheniformis pretreatment prevented LPS-induced intestinal injury by regulating the NLRP3 inﬂammasome. Furthermore, pretreatment with B. licheniformis tended to reverse the reduction of acetate and propionic acids in the cecal contents that occurred due to LPS stress. B. licheniformis markedly modulated the metabolites of saccharopine and allantoin from lysine and purine metabolic pathways, respectively. Overall, these data emphasize the potentiality of B. licheniformis as the dietary supplement to overcome the challenge of bacterial LPS in the animal and to enhance the food safety.